Regulacje dotyczące równego traktowania i zakazu dyskryminacji w zatrudnieniu tymczasowym - Wilczyński, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article discusses the legislation concerning equal treatment and non-discrimination in temporary employment in the light of the requirements of the Directive of the European Parliament and the European Council 2008/104/EC of 19 November 2008 on temporary agency work. The author outlines the legislative process related to the adoption of the directive, in particular the legal discrepancies, occuring both between social partners as well as between EU countries and analyzes the content of a directive adopted. Next, the author presents the Polish labor law provisions on equal treatment and non-discrimination. The main part of the article is devoted to the discussion of the adaptation of legal norms on equal treatment and non-discrimination contained in the Act of 9 July 2003 on the employment of temporary workers and other legal acts regulating this matter to the recommendations set out in the directive. The author analyzes the current level of compliance of Polish legislation to the requirements of the EU directive and present controversies in the literature as well as makes recommendations de lege ferenda.
Keywords: zatrudnienie tymczasowe; równe traktowanie; zakaz dyskryminacji; regulacje prawne